Municipal Accounting Information and Voting Behavior. - Ingram, Robert W.; Copeland, Ronald M. (The Accounting Review, 1981)
ABSTRACT: The purpose of this exploratory research is to assess empirically the potential usefulness of municipal accounting data for explaining voting decisions. The economic theory of voting behavior forms a conceptual foundation for examining the utility of accounting information for discriminating between mayoral election results. A stepwise discriminant analysis was used to develop multivariate models that distinguish between samples of cities clustered into three homogeneous groups on the basis of socio-demographic attributes. The dependent variable for the discriminant analysis was the outcome of elections for mayor in 113 cities with populations exceeding 25,000 in 1977, and the independent variables were municipal accounting ratios. Statistically significant discriminant functions were produced which correctly classified a greater-than-chance percentage of the election outcomes. These results suggest that municipal accounting numbers may provide useful information for explaining voter behavior since they measure the effects of municipal policy decisions consistent with voter assessments.